High-performance nanomaterials formed by rigid yet extensible cyclic β-peptide polymers. Issue 1 (December 2018) - Fears, Kenan; Kolel-Veetil, Manoj; Barlow, Daniel; Bernstein, Noam; So, Christopher; Wahl, Kathryn; Li, Xianfeng; Kulp, John; Latour, Robert; Clark, Thomas
Abstract Organisms have evolved biomaterials with an extraordinary convergence of high mechanical strength, toughness, and elasticity. In contrast, synthetic materials excel in stiffness or extensibility, and a combination of the two is necessary to exceed the performance of natural biomaterials. We bridge this materials property gap through the side-chain-to-side-chain polymerization of cyclic β-peptide rings. Due to their strong dipole moments, the rings self-assemble into rigid nanorods, stabilized by hydrogen bonds. Displayed amines serve as functionalization sites, or, if protonated, force the polymer to adopt an unfolded conformation. This molecular design enhances the processability and extensibility of the biopolymer. Molecular dynamics simulations predict stick-slip deformations dissipate energy at large strains, thereby, yielding toughness values greater than natural silks. Moreover, the synthesis route can be adapted to alter the dimensions and displayed chemistries of nanomaterials with mechanical properties that rival nature. Synthetic materials tend to excel in either stiffness or extensibility, whereas a combination of the two is necessary to exceed the performance of natural biomaterials. Here the authors present a bioinspired polymer consisting of cyclic β-peptide rings that is capable of transitioning between rigid and unfolded conformations on demand.